Awareness of sustainable finance development in the world from a stakeholder perspective - Rani, Asni Mustika; Dariah, Atih Rohaeti; Madhoun, Wesam Al; Srisusilawati, Popon (International Journal of Management and Sustainability, 2023)
Sustainable finance is one way to realize a new paradigm of sustainable development that incorporates social and environmental issues into economic calculations. However, in its implementation, each country faces different challenges in making and implementing policies to support sustainable finance. This study will analyze the public perception of Muslim-majority and Muslim-minority countries towards the implementation of sustainable finance in their respective countries and then analyze the stages of implementing sustainable finance. To analyze the level of implementation of sustainable finance, this study uses the concept of Attention-Interest-Desire-Action (AIDA). To collect data about the object of research using the methods of content analysis and field studies. Content analysis is all the efforts made by researchers in gathering information relevant to documents that explain the background of the existence of sustainable finance and its implementation in several countries. The field study is used to collect primary data regarding perceptions related to the context of sustainable finance, which can be used to determine the proportion of activities that substantially contribute to environmental objectives (climate change mitigation and adaptation efforts). Research results show that there is no difference in the views of respondents as development stakeholders regarding the implementation of sustainable finance in both Muslim-majority and minority countries. The majority of the two categories of country groups are still at the interest stage, reflected in high scores in normative statements and low scores in positive statements that describe real activities in running a sustainable finance system.